2021
DOI: 10.3389/fendo.2021.665811
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Long Non-Coding RNAs in Diabetic Vascular Complications

Abstract: Chronic metabolic disorders such as obesity and diabetes are associated with accelerated rates of macrovascular and microvascular complications, which are leading causes of morbidity and mortality worldwide. Further understanding of the underlying molecular mechanisms can aid in the development of novel drug targets and therapies to manage these disorders more effectively. Long non-coding RNAs (lncRNAs) that do not have protein-coding potential are expressed in a tissue- and species-specific manner and regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 137 publications
(209 reference statements)
1
30
0
Order By: Relevance
“…We identified the first lncRNAs regulated by AngII in rat VSMCs (RVSMCs) using integrated analysis of RNA-seq data with ChIP-seq datasets from histone H3K4me3 and H3K36me3 profiling [18]. Since then, several VSMC lncRNAs such as SENCR, MYOSLID and SMILR were described and found to play key roles in CVDs [19][20][21]. Another abundant nuclear lncRNA, NEAT1, was reported to be involved in VSMC phenotypic switching [22].…”
Section: Introductionmentioning
confidence: 99%
“…We identified the first lncRNAs regulated by AngII in rat VSMCs (RVSMCs) using integrated analysis of RNA-seq data with ChIP-seq datasets from histone H3K4me3 and H3K36me3 profiling [18]. Since then, several VSMC lncRNAs such as SENCR, MYOSLID and SMILR were described and found to play key roles in CVDs [19][20][21]. Another abundant nuclear lncRNA, NEAT1, was reported to be involved in VSMC phenotypic switching [22].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs were involved in various biological functions of fibrotic diseases [ 18–21 ]. This study identified 249 up-regulated and 169 down-regulated DELs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a high-fat diet, obesity, an aging population, and chronic levels of inactivity are all factors that contribute to the acceleration of the prevalence of diabetes in China. In recent years, accumulating evidence has demonstrated that lncRNAs play a key role in gene regulation and cellular function as well as the development of diabetes and its complications [15]. In 2012, Djebali et al >1,100 lncRNAs expressed specifically in human pancreatic islets and purified β-cells, providing the first evidence that lncRNAs are associated with diabetes [16].…”
Section: Discussionmentioning
confidence: 99%